5(2-3)=3(3x+2)

Simple and best practice solution for 5(2-3)=3(3x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2-3)=3(3x+2) equation:


5(2-3)=3(3x+2)

We simplify the equation to the form, which is simple to understand
5(2-3)=3(3x+2)

Simplifying terms in parentheses
5*(-1)=3*(3x+2)

Reorder the terms in parentheses
+(-5)=3*(3x+2)

Remove unnecessary parentheses
-5=+3+*(+3x+2+)

Reorder the terms in parentheses
-5=+(+9x+6)

Remove unnecessary parentheses
-5=+9x+6

We move all terms containing x to the left and all other terms to the right.
-9x=+6+5

We simplify left and right side of the equation.
-9x=+11

We divide both sides of the equation by -09 to get x.
x=-1.22222222222

See similar equations:

| 3x-x^3=0 | | 2x+11=3x | | x+5=x+7-2 | | 3x-1=-x-1 | | 9x-3=-2x+19 | | 39=.5(17x+6-7x-2) | | 5*0+0+11*-0.09090909091+-0.5454545455*0*-1=1 | | (5x+x+(11*(-0.09090909091+-0.5454545455x)))*-1=1 | | (5x+x+(11*-0.09090909091+-0.5454545455x))*-1=1 | | -2b+3b=-1 | | (5x+x+11t)*-1=1 | | (5x)+x+11t*-1=1 | | (5x^2)-5x^2=0 | | 25x+24y=11.1 | | (5x^2)+5i=0 | | 4.0x=13.2 | | 98x*4t=5 | | 3x-1=7x+1 | | 8.8x=30.8 | | 10=-z+3 | | 8x^2-8x+77=0 | | k*2.7=21 | | h*0.3=19 | | 8m=2(j+4+3m) | | 49.6+5*x=(10+x)5.4 | | x^5+4x^3-2x^2-8=0 | | 49.6+5*x=5.4(10+x) | | 49.6+10*x=5.4(10+x) | | y=4x^3-7x-3x^2+6 | | 28.8+x*6=(6+x)(5.4) | | 24.78+x*6=(6+x)(5.4) | | 24.78+x*6=6+x(5.4) |

Equations solver categories